Pharmacoeconomic analysis of biological disease modifying antirheumatic drugs in patients with rheumatoid arthritis based on real-world data from the IORRA observational cohort study in Japan. Issue 2 (4th March 2017) - Tanaka, Eiichi; Inoue, Eisuke; Yamaguchi, Rei; Shimizu, Yoko; Kobayashi, Akiko; Sugimoto, Naoki; Hoshi, Daisuke; Shidara, Kumi; Sato, Eri; Seto, Yohei; Nakajima, Ayako; Momohara, Shigeki; et al.
Abstract: Objectives : To evaluate the cost-effectiveness of biological disease modifying antirheumatic drugs (bDMARDs) in patients with rheumatoid arthritis (RA) in a real-world setting in Japan. Methods : We used a state-transition model and parameters were determined from RA patients registered in the Institute of Rheumatology, Rheumatoid Arthritis (IORRA) cohort study on 421 patients who had failed at least one DMARD and started either 1 of 4 bDMARDs (bDMARD group; adalimumab, etanercept, infliximab, and tocilizumab) or methotrexate (control group). bDMARD group was evaluated as two groups: sequence of any 1 of 4 bDMARDs with and without tocilizumab. The incremental cost-effectiveness ratios (ICERs) for bDMARD group were estimated using base-case analysis, probabilistic sensitivity analysis (PSA) and scenario sensitivity analyses. Results : ICERs of bDMARD group with or without tocilizumab were $38, 179 and $48, 855, respectively. By PSA, these sequences had respective probabilities of 86.8% and 75.1% of falling below the assumed cost-effectiveness threshold of $50, 000 in Japan. Scenario sensitivity analyses showed that the best population for initiating bDMARD was RA patients less than 50 years old with Japanese version of HAQ between 1.1 and 1.6 and using tocilizumab as the bDMARD. Conclusion : bDMARDs were cost-effective for RA patients based on a real-world setting in Japan.